The Impact of Academic Titles of Board Member and Directors Over the Performance of Companies Traded at B3 - Marcelo Perlin; Guilherme Kirch; Daniel Vancin; Mauro Mastella (BBR: Brazilian Business Review)
Previous studies show that the academic qualification of directors affects the performance and risk of companies. However, such evidence is based on a restricted set of information regarding the academic background and scientific output of directors. In this paper we investigate whether the academic titles of directors and board members impact the performance of publicly traded companies. The sample comprises 133 non-financial companies, from 2010 to 2018, consolidating information extracted from the financial exchange and the Lattes platform. Our results show that academics are more common on large boards of publicly controlled companies. Overall, the estimation results do not provide convincing evidence for the impact of academics over corporate performance. However, particularly, we see that only the presence of doctors with degrees obtained abroad affects positively the profitability and negatively the risk of the studied companies. Other academic attributes of the board impacted companies’ risk but not their profitability.